Transnational masculinities in situ: Singaporean husbands and their international marriage experiences - Cheng, Y (Wiley, 2011)
While most work is still largely concerned with women's experiences and places their narratives under the spotlight of the intellectual domain, there is undoubtedly an increasing realisation that missing out on men's narratives is akin to missing out a piece of the puzzle. The demographic approach tends to portray men who enter international marriages as ‘failed men’ and ‘losers’ in local ‘marriage markets’, and very little is revealed about the multiple positions and strategies taking place in these men's marital lives. This paper adopts an expansive view of transnationalism that argues for an understanding of subjectivities and identities as situated/rooted and mobile simultaneously. Drawing on the argument that ‘mobile’ identities are not necessarily achieved only by bodies on the move, and unsettling the binary between movement/non-movement and mobility/immobility, I demonstrate how non-migrant men in international marriages construct their masculine selves across transnational topographies in relation to a range of spaces and times. This attunement to how space is temporalised reveals a series of different times and spaces folded into and unfolded from each other in how narratives are articulated by the Singaporean men in this study. By attending to how temporal modalities of the past, present and future are actively mobilised in the construction of masculine selves in the Singaporean husbands' narratives, I argue that despite their in situ position within transnational topographies, their masculine identities and subjectivities are not bounded by space and time, but rather draws on them to become realised. To demonstrate this argument, this study draws on the narratives collected through in-depth interviews with 15 Singaporean husbands who have married Vietnamese women.